ON THE STUDY OF CHAINS SOFT SETS, SOFT ORDERED SETS AND SOFT SEMILATTICES (FUDMA JOURNAL OF SCIENCES, 2022)
In this paper, we study the concept of chains soft sets and set-valued function of chains soft sets. The definitions of chains soft sets or linear order or total order soft set are given. The notions of binary relation of comparability of the elements of set-valued functions are also discussed. Linearization’s of a partial order soft set are also defined. The definition and some algebraic structure of soft semilattice are also given.
Keywords: set-valued, notions, partial order, Linearization